Analisis Soal TOSA (Test of Standard Arabic) Mengacu Pada CEFR (Common European Framework of Reference For Language) - Muhammad Zaenuri; Muhammad Nur Kholis; Anisatul Barokah (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2020)
This study aims to explore and analyze the TOSA (Test of Standard Arabic) questions as an instrument to measure the Arabic language competence of students at IAIN Surakarta. This research uses a qualitative approach. The results of the study showed: 1) TOSA was prepared using an integrative, communicative and pragmatic approach; 2) TOSA is a type of standard test used to measure the Arabic language competency testee, not the testee's mastery of the material that has been taught; 3) TOSA competency standard refers to CEFR (Common European Framework of Reference for Language) according to its part, so fahmu al-masmu 'is equivalent to A1-C1 CEFR, fahmu at-tarakib al-lughawiyyah is equivalent to A1-B2 CEFR, and fahmu al-maqru' is equivalent to A1-C1 CEFR.